Selection value of nonpubescent soybean lines [Glycine max (L.) Merrill] for different uses - Л. Г. Білявська; Ю. В. Білявський; А. О. Діянова; Ю. Є. Гарбузов (Plant Varieties Studying and Protection)
Purpose. Create a new source material of soybeans without pubescence, determine its selection value for the efficient use of processed products in animal nutrition, which will ensure high productivity of the latter. Quantitative and qualitative indicators of seeds are important economic and valuable features. The lack of pubescence on plants is unique.